2017
DOI: 10.3892/mmr.2017.7674
|View full text |Cite
|
Sign up to set email alerts
|

Expression of NR1 and apoptosis levels in the hippocampal cells of mice treated with MK-801

Abstract: The aim of the present study was to investigate the characteristics of N‑methyl‑D‑aspartate receptor R1 (NR1) expression and apoptosis in the nerve cells of the hippocampus in schizophrenia‑like mice. C57BL/6 mice were randomly allocated to the following groups: i) Blank group; ii) MK‑801 group; iii) MK‑801+NMDA group, according to body weight. The NMDAR antagonist, MK‑801 (0.6 mg/kg/d) was intraperitoneally injected daily for 14 days to induce a schizophrenia‑like phenotype mouse model, and the effect of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Numerous studies have confirmed that NMDAR antagonists induce SZ-related behavior (Jeon et al, 2017). Meanwhile, our previous studies (Ding et al, 2017(Ding et al, , 2019 and other work (Seillier and Giuffrida, 2009;Jacklin et al, 2012;Karamihalev et al, 2014;Li et al, 2016) found cognition impairment and alterations in anatomical and neurochemical aspects in a mouse subchronic model of SZ induced by the intraperitoneal injection of MK-801 for 14 consecutive days. Given that SZ is a chronic psychiatric disorder, subchronic administration with MK-801 might better represent the enduring cognition deficits of SZ (Karamihalev et al, 2014;Xiu et al, 2014), meaning it may serve as a robust model for the disease.…”
Section: Discussionmentioning
confidence: 74%
“…Numerous studies have confirmed that NMDAR antagonists induce SZ-related behavior (Jeon et al, 2017). Meanwhile, our previous studies (Ding et al, 2017(Ding et al, , 2019 and other work (Seillier and Giuffrida, 2009;Jacklin et al, 2012;Karamihalev et al, 2014;Li et al, 2016) found cognition impairment and alterations in anatomical and neurochemical aspects in a mouse subchronic model of SZ induced by the intraperitoneal injection of MK-801 for 14 consecutive days. Given that SZ is a chronic psychiatric disorder, subchronic administration with MK-801 might better represent the enduring cognition deficits of SZ (Karamihalev et al, 2014;Xiu et al, 2014), meaning it may serve as a robust model for the disease.…”
Section: Discussionmentioning
confidence: 74%
“…Dysregulation of apoptosis, reduced expression of the antiapoptotic protein Bcl‐2, and an elevated ratio of the proapoptotic protein Bax/Bcl‐2 have all been seen in both clinical investigations and postmortem brain tissue examinations of SZ patients (Jarskog et al, 2004). MK‐801 induced apoptosis of hippocampal cells and downregulation of Bcl‐2 expression in an SZ‐like animal model (Ding et al, 2017). Furthermore, it has been demonstrated that exposure to NDMA receptor antagonists during perinatality results in a persistent disruption of hippocampus apoptosis (Jarskog, 2006; Jevtic et al, 2016; Osacka et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 40 mice were randomly divided into four groups (10 mice per group) as follows: Control group (Control), MK-801 group (MK-801), MK-801 plus A 2B AR agonist group (MK-801 + BAY) and MK-801 plus A 2B AR antagonist group (MK-801 + PSB). The SCZ model was established according to a previously described method (26). Briefly, mice were injected intraperitoneally with MK-801 (0.6 mg/kg/day; cat.…”
Section: Methodsmentioning
confidence: 99%